Management of Mukhapaka with Ayurvedic Treatment with special reference to Stomatitis-A Case Report - Chaya , C; Jyoti (International Research Journal of Ayurveda & Yoga, 2022)
The mouth is a window to the body’s health. It can show signs of nutritional deficiencies or general infection. Oral health is an integral component of general health and well being for all ages. Mukhapaka is a commonest disease of oral mucosa found in India as well as all over the world. Mukhapaka is nothing but a recurrent mouth ulcer or Stomatitis.Oral ulceration is encountered frequently in our daily practice because of over consumption of extremely pungent and spicy food, chewing of chemical agents like Tobacco-Gutkha and also Vitamin deficiency.Stomatitis is curable & not considered threat to life but these ulcers have significant negative impact on the oral health and affecting the quality of life. It also affects normal activities like eating & swallowing. Sometimes brushing & talking also becomes painful. In present era, world is looking at Ayurveda with the hope that it is going to provide good asset to the treatment of ailing humanity. In Ayurveda various treatment modalities are described for Mukhapaka.. I have selected one of them to establish efficacy of Gandusha and Pratisarana on Mukhapaka in my present case study.